Beyond Biblical Literacy: Developing Readerly Readers in Teaching Biblical Studies. (December 2014) - Stack‐Nelson, Judith
Abstract Theological education in biblical studies often has focused on information, but it needs to emphasize developing skills and sensibilities in students that will produce confident, imaginative, and attentive readers. To form readers with a disciplined imagination—what we are calling "readerly readers"—educators need to inculcate skills and sensibilities that will enable students to interact with the text as a living voice, rather than as an object to be mastered, and to allow the text to provoke difficult, profound, or long‐term questions.